Evidence Based Service Policy In Libraries: The Reality Of Digital Hybrids - Yildiz, Asiye Kakirman (Qualitative and Quantitative Methods in Libraries; Vol 5 No 3 (2016): September 2016 Issue, 2016)
Evidence based library management is one of the most significant contemporary developments in professional library practice. Although they are non-profit making organisations, the main aim of libraries is to satisfy their customers, that is, the library users. This aim is achieved as long as the needs and expectations of the users are met. For this reason, the libraries must know their users very well and must provide a service which fulfils their needs and expectations. Therefore, rather than following fashionable or popular approaches which are discussed in the literature, libraries should carry out their own analyses and develop an evidence-based service policy for their users. In the studies made by Mark Prensky, individuals are classified and evaluated according to their technological abilities and skills into 2 group as “digital natives” or “digital immigrants” and since this time the subject has cantinued to be discussed. According to Prensky, those born before 1980 should be classed as digital immigrants and those born after 1980 are classed as digital natives. The digital natives were literally born into a world of knowledge and technology. The most important characteristic of digital natives is that not only do they perfom more than one function on a single device simultaneously. In this study it was analyzed that whether the students that study in the different faculties of Marmara University are digital natives or not. The study also examines how to user group of “digital hybrids” has an effect on the management procedures of the library and how this element affects the management of the other elements. The questionnaire that formed the basis of this study was applied to 382 students and their approach to accessing information was analysed. After the completion of the survey, a new category of “digital hybrids” was proposed; it is suggested that digital natives, who in the literature are described as those born after 1980, should in fact be defined as those born after the year 2000, digital immigrants should be defined as those born before 1970 and yhose between from 1970-1999 should be described as digital hybrids. The result of this study important that also, rather than the fashionable approaches in the literature, we need to consider the needs and expectations of the users; digital natives, digital immigrants or digital hybrids and to adopt an evidence-based approach to service policy development.